Labor market consequences of trade openness and competition in foreign markets - Daniel Chiquiar; Enrique Covarrubias; Alejandrina Salcedo (Banco de México, 2017)
We analyze the labor market consequences of international trade, using the evidence provided by the behavior of Mexican labor markets after the introduction of NAFTA in the nineties and the accession of China to the WTO in 2001. Following an approach close to that proposed by Autor, Dorn and Hanson (2013), we use the local market variation on exposure to international markets to identify the effects of these events. We show that NAFTA integration reduced unemployment, and boosted employment and wages. Chinese competition tended to have the opposite effect. Additionally, we find that the labor market responses to international trade are heterogeneous across regions in the country, being significantly stronger in the regions closer to the U.S. border.
Keywords: E24; F14; F16; 330; International trade and labor markets; local labor markets; Mexico; NAFTA; Chinese competition